Ensuring Food Security of Kazakhstan by the Integrated Water Resources Management - M. N. Sennikov; G. E. Omarova (Проблемы постсоветского пространства, 2018)
One of the main objectives of the states located in the territory of arid regions is the timely obtaining solid and exhaustive data, the forecasts connected with the climatic phenomena, allowing to provide the timely organization of works on safety and prevention of possible damage to agriculture and in general all national economy. This task can be solved only in the presence of well adjusted, system of collecting, processing and implementation of information. For ensuring food security of the country it is necessary to provide the integrated control system of water resources at timely coordination of all stages of regulation on the basis of multiplefactor monitoring of indicators.The increasing deficiency of water resources in basins of the cross-border rivers of the arid region of the republic demands introduction of the new scheme of management which would allow their use in the conditions of limitation.Due to the formation of the new independent states need of improvement of the existing organizational forms of ownership and water resources management of the cross-border rivers which will be proved on rules of international law and the best practice of cooperation pools when sharing taking into account the interests of the adjacent countries of the region is caused. The main priority direction of the arid region of the republic is development of long-term programs, proved on a package of measures and actions for water economy, maintaining her quality and increase in an ecological situation of water management systems.Now each country develops own strategies of water use which leads to strengthening of the competition for water, sharpening of deficiency of water and environmental problems, both on interstate, and at the regional level. Further, the issue of ensuring food security in the conditions of impact of climate change on agriculture is resolved. The existing risks connected with climate changes and ways of adaptation of agricultural production have been defined.The main national policy of the republic is aimed at ensuring the food security with the balance of production. Considering features of the region and the available restrictions as: existence of the irrigated lands, their efficiency, limitation of water resources and their effective use has to be proved on universal introduction of water-conservation technologies of irrigation when carrying out complex reconstruction of irrigating systems and the principles of the integrated use of water resources.